Temperature-control system - Nor Mazlee, Norazmi (2009)
This project title is ‘Temperature-Control System’ which is a particular system for server room. For the circuit, it consists of temperature sensor, PIC, LCD, driver circuits, AC air heater and AC motor. Three drivers are used for triggering process to switch on the AC heater and another two are for triggering levels of the motor. This motor will operate based on two temperature ranges and that means, it has two levels of speed. The function of this system is for controlling the temperature value inside of a regular room automatically. It will operate based on the values or ranges of temperature in the room which is detected by the temperature sensor.If the temperature in the first range (0ºC to 15ºC ),the air heater will be operated to heat the server room which in very cold temperature.If it is in the second range(16ºC to 25ºC) this system will not be enabled because it’s achieving normal temperature range.If temperature in range 26ºC to 40ºC,motor will be triggered for level 1 to decrease the temperature value. If it is more than 40ºC, the motor will be triggered for level 2 and its speed becomes faster at this level. The both output devices are important to maintain the temperature value in the room .This system can be categorized in automatic system class and solve users’ problem.The problem always happen if air-conditioner broke down and definitely, the room becomes hotter or temperature increases. Besides that, temperature becomes too cold and influenced by weather from outside of the sever room. With that, the motor and air heater are important to keep maintaining the sever room in suitable temperature range. This system has temperature sensor which may detect the surrounding temperature and the outputs are operated based on the temperature ranges.Programming of the PIC is a important basic to read data or accept signal from the sensor .In the same time,it maintains the temperature inside of the room and make it suitable for user.